2015 White Paper on recent issues in bioanalysis: focus on new technologies and biomarkers (Part 1 – small molecules by LCMS). (November 2015) - Welink, Jan; Fluhler, Eric; Hughes, Nicola; Arnold, Mark; Garofolo, Fabio; Bustard, Mark; Coppola, Laura; Dhodda, Raj; Evans, Christopher; Gleason, Carol; Haidar, Sam; Hayes, Roger; et al.
The 2015 9th Workshop on Recent Issues in Bioanalysis (9th WRIB) took place in Miami, Florida with participation of over 600 professionals from pharmaceutical and biopharmaceutical companies, biotechnology companies, contract research organizations and regulatory agencies worldwide. It is once again a 5-day week long event – a full immersion bioanalytical week – specifically designed to facilitate sharing, reviewing, discussing and agreeing on approaches to address the most current issues of interest in bioanalysis. The topics covered included both small and large molecules, and involved LCMS, hybrid LBA/LCMS, LBA approaches including the focus on biomarkers and immunogenicity. This 2015 White Paper encompasses recommendations that emerged from the extensive discussions held during the workshop, and is aimed to provide the bioanalytical community with key information and practical solutions on topics and issues addressed, in an effort to advance scientific excellence, improve quality and deliver better regulatory compliance. Due to its length, the 2015 edition of this comprehensive White Paper has been divided into three parts. Part 1 covers the recommendations for small molecule bioanalysis using LCMS. Part 2 (hybrid LBA/LCMS and regulatory agencies' inputs) and Part 3 (large molecule bioanalysis using LBA, biomarkers and immunogenicity) will also be published in volume 7 of Bioanalysis, issues 23 and 24, respectively.